Cochlear implantation in a patient with combined renal and liver transplantation. (November 2014) - Mahalingam, Sridhayan; Mathew, Rajeev; Patel, Sharmila; Harris, Robert; Selvadurai, David
<x content-type="archive" xml:space="preserve">Abstract</x> Objective and importance Patients who have undergone solid organ transplantation and continuing immunosuppressant medication are at a higher risk of wound problems and infections following cochlear implantation. This risk is theoretically even further increased in multi-organ transplant recipients due to the increased doses of immunosuppressive medications that these patients are administered. Clinical presentation and intervention Here, we present the first reported case of successful cochlear implantation in a patient who had previously undergone successful combined liver and kidney transplant. She had no significant complications from the surgery and had good audiological outcomes 3 months post-operatively. Conclusion As we continue our advances in the use of cochlear implant technology, our report adds to the growing evidence of its benefits in transplant recipients. However, there are important pre- and peri-operative considerations in this group of patients which can improve safety and outcome.